Flexible Bronchoscopy in Children: An Overview (Dhaka Shishu (Children) Hospital Journal, 2024)
Bronchoscopy is a dynamic diagnostic tool that has continually advanced alongside the rapid progression of medical technology. It offers a comprehensive evaluation of the upper and lower airways, catering to a wide range of respiratory concerns. Over the course of numerous decades, bronchoscopy has played a pivotal role in the field of pediatric pulmonology, providing invaluable diagnostic and therapeutic options that extend well beyond the boundaries of this specialized medical domain. The purpose of this article is to consolidate the existing knowledge and explore the diverse interdisciplinary facets of pediatric bronchoscopy, with the ultimate goal of establishing a consensus on the safe and effective technical execution of this procedure. The intension is to create a standardized foundation for its practical application.DS (Child) H J 2023; 39(1): 49-55